Framing The Covid-19 Vaccine Through Social Media in Millennials (Study on Instagram Account of The Ministry of Health of The Republic of Indonesia) - Suaib, Nadinta Rafifah; Dunan, Amri (International Journal of Educational Research & Social Sciences, 2021)
In controlling the COVID-19 pandemic, the Indonesian government conducts COVID-19 vaccination activities. The Ministry of Health provides information about the COVID-19 Vaccine by utilizing the help of Instagram's social media. The purpose of this study is to analyze the framing process of COVID-19 vaccine news conducted by the Ministry of Health on Instagram social media accounts, analyze the frames of the COVID-19 Vaccine, identify factors that influence the framing process, and identify the influence of COVID-19 Vaccine framing on millennials' responses related to the COVID-19 Vaccine. The result is that there are two things done by the Ministry of Health in the framing process, namely choosing facts and writing down facts with selected facts related to health in general and starting to highlight facts related to the COVID-19 pandemic in November 2020. The four facts highlighted by the news writer are 'vaccine safety', 'vaccine halalness', 'vaccine quality', and 'vaccine effectiveness'. The factor of this framing is the necessity of the Ministry of Health as a public body to provide information as clearly as a result of public doubts about the safety, halalness, effectiveness, and efficacy of the COVID-19 Vaccine as the many hoaxes news circulating in the community. Based on quantitative data, there is an 18.3% influence on the framing of COVID-19 vaccine news on millennials' response to the COVID-19 Vaccine.